(untitled) (Bangladesh Journal of Agricultural Research, 2013)
A study was conducted at the Floriculture Research Field of Horticulture Research Centre of Bangladesh Agricultural Research Institute (BARI) during the period from November 2006 to May 2008 to determine the optimum rate of N and K for better growth and yield of corm and cormel of gladiolus. The treatment combination N150 K200 kg/ha produced the longest plant (42.1 cm), the broadest leaf (1.93 cm), the maximum percentage of spikes (88.1%), and corm (97.6%), the heaviest and the largest corm (19.5 g and 4.11 cm, respectively), cent percent flowering sized corm, and the highest corm number and cormel yield (1,20,000 and 1.66 t/ha, respectively). The corm produced from this treatment combination also showed better performances in the next year in respect of plant emergence (100%), florets/spike (13.1), spike and rachis length (82.2 cm and 45.4 cm, respectively), flower stick weight (57.1 g) and percentage of flower sticks (113%). DOI: http://dx.doi.org/10.3329/bjar.v37i4.14385 Bangladesh J. Agril. Res. 37(4): 607-616, December 2012